(untitled) (ouvirOUver, 2022)
Tradução de "Environmental presence", de Gabriella Giannachi. In: GIANNACHI, Gabriela; KAYE, Nick; SHANKS, Michael (org.). Archaeologies of Presence: Art, Performance and the persistence of being. Londres: Routledge: 2012. P. 50-63.